The Utilization and Strengthening the Market Digital Management for Batik Cianjur Community to Spread the Market Consumers of Batik Cianjur - Destiana Husnul Chotimah Viena; Muhammad Adikuncoro; Pupu Jamilah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Community Service Program - Pengabdian Masyarakat Pemula (PMP) is a program that aims to help Batik Cianjur Community who are members of Batik Cianjur Community to marketing Batik products more broadly, especially with introducing the products that has a significant meaning of local culture and wisdom to the world through https://www.komunitasbatik.com . This website will be managed independently by the Cianjur Batik community which is driven by Dahlia Batik Genturan, Rajafa Batik, and VienaCraft. The method it used in this program was through the assessment to identify the needs of target partners, website content design (blueprint), promotional  content workshop and maintenance, straightening community management. The batik craftsmen, members of Batik Cianjur Community will be given a training to establish the website operations and content management skills, business management and organization management. With the strategy of optimizing the utilization of batik community websites and intensify digital marketing management in the Batik Cianjur community, it is expected to improve the knowledge, insight, skills, and productivity of Cianjur batik craftsmen so that it has an impact on increasing the Batik Cianjur consumers. The result of this PKM - PMP is that Partners can independently manage the komunitasbatik.com website as a digital marketing media both in managing promotional content and managing transactions digitally. In addition, waste from batik cloth can be reprocessed into accessories that have economic value to increase benefits and income for Partners. Although there are several obstacles in the implementation of this PKM - PMK, including the difficulty in determining the meeting time because it must be adjusted to the activities of batik craftsmen, this program can run according to the planned targets and timelines. Partners can make maximum use of the website and strengthen digital marketing management to expand the Cianjur batik consumer market. Eventually, the success of this program will be disseminated to the other batik craftsmen widely and sustainably.